2014
DOI: 10.1177/1753425913518225
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-driven modulation of NK cell expansion, intracellular cytokine expression and cytotoxic activity

Abstract: During Helicobacter pylori (Hp) infections, innate immune cells may be positively or negatively modulated by Hp compounds or by Hp-induced cytokines. We have shown previously that the natural cytotoxic activity of PBMC was lower in Hp-infected [Hp(+)] than Hp-uninfected individuals [Hp(-)]. Here, we asked whether the Hp-modulated cytotoxic amplitude is associated with changes in the number of NK cells, their activation or intracellular cytokine expression. Flow cytometry immunophenotyping of PBMC was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…However, it has been shown that H. pylori LPS is able to downregulate the lymphocyte blastogenic response, probably due to the interference with the process of macrophage maturation[46-48,94]. It also downregulates the phagocytic potential of macrophages[44] and decreases the cytotoxic activity of NK cells[45,68]. In the gastric epithelium, colonized by pathogenic microorganisms, including H. pylori , probably IL-33 acting as an alarming molecule can induce the signalling beneficial for tissue recovery due to a short-term increase in endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that H. pylori LPS is able to downregulate the lymphocyte blastogenic response, probably due to the interference with the process of macrophage maturation[46-48,94]. It also downregulates the phagocytic potential of macrophages[44] and decreases the cytotoxic activity of NK cells[45,68]. In the gastric epithelium, colonized by pathogenic microorganisms, including H. pylori , probably IL-33 acting as an alarming molecule can induce the signalling beneficial for tissue recovery due to a short-term increase in endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…This is by reducing the host immune response mechanisms including phagocytosis[44], Natural Killer cells activity[45] and proliferation of T lymphocytes[46-48]. LPS through binding with dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) may interfere with the development of specific immune response[49,50].…”
Section: Introductionmentioning
confidence: 99%
“…The primary host immune response mechanisms, such as phagocytosis and natural killer (NK) cell activity, have been found to be downregulated by H. pylori LPS[17,18,39,40]. Adaptive immunity is also targeted by H. pylori compounds[1,15,41,42].…”
Section: Microbiological Aspects Of H Pylorimentioning
confidence: 99%
“…Previous studies showed that H. pylori LPS possesses immunomodulatory properties that diminish the effectiveness of the phagocytosis, cytotoxic activity and the expansion of NK cells and T lymphocytes[40-42]. …”
Section: Introductionmentioning
confidence: 99%